2011
DOI: 10.1242/dev.062737
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic control of head mesoderm patterning

Abstract: SUMMARYThe embryonic head mesoderm gives rise to cranial muscle and contributes to the skull and heart. Prior to differentiation, the tissue is regionalised by the means of molecular markers. We show that this pattern is established in three discrete phases, all depending on extrinsic cues. Assaying for direct and first-wave indirect responses, we found that the process is controlled by dynamic combinatorial as well as antagonistic action of retinoic acid (RA), Bmp and Fgf signalling. In phase 1, the initial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 77 publications
4
88
0
1
Order By: Relevance
“…to the heart- and tail bud-associated progenitor fields) [16]. This action is mediated by RAR/RXR heterodimers binding to a repressive DR2 RARE located upstream of the FGF8 gene [22, 23] that, in turn, activates CYP26 expression both anteriorly and posteriorly to limit the extent of RA activity [16, 24, 25]. In addition, the expression of CYP26A1 and CYP26B1 have been shown to be dependent on RA activity, thereby generating a CYP26 -controlled negative feedback loop in RA sensitive tissues to reduce the overall amount of available RA [9, 18, 26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…to the heart- and tail bud-associated progenitor fields) [16]. This action is mediated by RAR/RXR heterodimers binding to a repressive DR2 RARE located upstream of the FGF8 gene [22, 23] that, in turn, activates CYP26 expression both anteriorly and posteriorly to limit the extent of RA activity [16, 24, 25]. In addition, the expression of CYP26A1 and CYP26B1 have been shown to be dependent on RA activity, thereby generating a CYP26 -controlled negative feedback loop in RA sensitive tissues to reduce the overall amount of available RA [9, 18, 26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…In these previous studies, the expression patterns of pax1/9 cognates were affected, corresponding to defects in the posterior pouches caused by the lack of RA (Wendling et al, 2000). Additionally, Tbx1 reportedly modulates the dynamics of RA signaling in the developing vertebrate head by regulating Cyp26 genes, which encode RA-degrading enzymes (Roberts et al, 2006;Bothe et al, 2011). Regarding the function of Fgf signaling in pouch formation, it has been shown that its inhibition causes complete loss of the pharyngeal pouches forming posterior to the second arch (Abu-Issa et al, 2002;Crump et al, 2004).…”
Section: Impact Of Pax1 On Pharyngeal Segmentation and Derivativesmentioning
confidence: 99%
“…Likewise, inhibition of FGF signaling using retinoic acid (RA) downregulated MyoR and Tbx1. Thus, low levels of RA promote FGF signaling and consequently MyoR and Tbx1 activation (Bothe, Tenin, Oseni, & Dietrich, 2011; Scheven von, Alvares, Mootoosamy, & Dietrich, 2006). FGF signaling has been found to be an important regulator of myogenesis in the limb.…”
Section: Fibroblast Growth Factor Signalingmentioning
confidence: 99%